A Study of Sukuk Bond market-making at the London Stock Exchange, 2011-20 - Ariff, Mohamed *; Cheong, Calvin W. H. * (2021)
This paper has the objective of studying the Islamic bond market in the London Stock Exchange (LSE) which surprisingly is a latecomer, 21 years after the first Islamic bond that was listed in 1990. London took time to assess the market debut although it is the Bank of England that paved the way for the level-playing-field regulations to create Islamic banking. The Shariah-compliant Islamic bonds known as sukuk are traded in 23 plus markets and there are 2,340 such faith-based issues as at 2021. The total funds raised to-date in such exchange-traded Islamic bond exchanges over 31 years is worth US$526 billion with an average issue size of US$220 million each globally. London has raised US$50 billion with some 125 issues during its ten-year history. With perhaps the fastest growth rate among all exchanges, LSE chalked a growth rate of 56% per year, an extraordinary achievement with an average issue size 2 times bigger than the world average. In contrast, the global sukuk market growth rate is about 8% to 12% per year. The growth rate of the much older and larger mainstream bond market in some 137 market places is in the range of 4% to 5% per year. That makes it interesting to study the London market to understand its institutional structure, market-making efforts, liquidity, issuance effect and other pertinent aspects